Rekonfigurasi Ruang Sakral di Era Digital: Mediatisasi, Otoritas Keagamaan, dan Konstruksi Makna Daring - Musalim Ridlo (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2026)
This article examines how digital mediatization reconfigures sacred space, religious authority, and religious meaning-making. Using a qualitative library-based approach, it engages scholarship on mediatization, simulacra, networked religion, and online religious communication. The article argues that digital religion should not be seen solely as either desacralization or expanded access, but as an ambivalent reordering of religious life. It identifies three interrelated dynamics: the remediation of ritual, the platformization of religious authority, and the algorithmic shaping of religious experience. The analysis shows that digital media do not simply replace physical sacred space; instead, they generate hybrid and multisited forms of religiosity in which practice, legitimacy, and meaning are continuously negotiated. At the same time, digital platforms subject religion to pressures of visibility, performance, commodification, and fragmentation. Digital religion is therefore best understood as an epistemic reconfiguration of contemporary religious life